Food Industry Wastes for the Development of Innovative Functional Pet Food - Pame, Kuleswan; Laskar, S. K.; Handique, K. M.; Choudhury, S. (International Journal of Bio-resource and Stress Management, 2025)
The review was aimed to discuss the beneficial effect various bioactive compounds harnessed from by-products of both plant and animal origin in the development of functional pet food for dogs . Functional foods occupied a special place in the science of food technology and nutrition. Bioactive compounds became one of the most trending research areas in the field of functional food. This review aimed to highlight the role of various bioactive compounds harnessed particularly from by-products of agro-food-processing and meat processing industries in the development of innovative functional foods for pet nutrition. Additionally this article featured various studies to support the positive impact on the health of pet animals. Functional foods provided proven health benefits to both humans and animals, when consumed on a regular basis. Studies have demonstrated the effect of bioactive compounds in functional pet food formulation such as modified gastrointestinal physiology, promoted beneficial biochemical changes, minimized the risk of developing specific diseases, and improved nutritional stability. These effects were achieved through varied properties such as antioxidant, anti-inflammatory, antimicrobial, antiatherogenic, antithrombotic, cardioprotective, and vasodilatory properties present in various bioactive components obtained from both plant and animal sources. However, further research was required to up-scale production process of bioactive compounds for industrial application and regulatory compliance. This review article threw lights to pet food manufacturers in the development of functional pet foods. It also addressed the need of utilization and up-cycling of food waste for value addition for sustainability of food processors.